Black faculty do it all : a moment in the life of a blackademic - Tomlin, Antione D. (Research, theory, and practice within academic affairs., 2023)
"Black Faculty Do It All: A Moment in The Life of a Blackademic is a work that creates space for Black academics or Blackademics to share their experiences navigating workspaces within higher education and their experiences as Black professionals. The primary goal of this book is to provide insight into Black faculty experiences told by Black faculty. While frequently, Black faculty can feel silenced within the academy, this book offers a platform for all Black faculty's voices to be heard loud and clear. Contributing authors share advantages and challenges they experience as Blackademics and the impact these experiences have on their well-being and career trajectory. Moreover, the authors provide insight and advice on how current and potential Blackademics can succeed and thrive, even with all the barriers or obstacles they face. Contributing Blackacdemics collective has a wealth of knowledge and disciplines represented, expertise, position full-time and part-time, and years of experience in higher education. Additionally, authors also come from all over the United States. With this range of expertise and knowledge, authors also provide advice, strategies, and ways of being for institutions to support their Black faculty and for Black faculty to support themselves. Despite all the efforts with diversity, equity, inclusion, and anti-racist initiatives, Black faculty is still not okay (Tomlin, 2022). While many Black faculty have challenges in the profession, we are not suggesting that all Black faculty face the same issues. In fact, "the idea that all Black faculty would share the same experiences is a fallacy, and the insinuation is as dangerous as assuming that all Black people are the same" (Allen & Steward, 2022, p. 2). Moreover, this book serves as a space for contributing authors not to speak for all Black faculty but themselves. As editor and a Blackacdemic myself, I encouraged and pushed all contributing authors to stand in their Blackness unapologetically. This book is the outcome of Black faculty loving and supporting Black faculty. Higher education institutions, colleagues, and other stakeholders can learn a great deal from the narratives and experiences shared to look at the intentional recruitment, retention, and psychological well-being of Black faculty. Thus, Black Faculty Do It All: A Moment in The Life of a Blackademic is positioned to be a must-read for all higher education professionals, institutions, and stakeholders looking for strategies to do right back for Black faculty"--